The Current Situation of Ideological and Political Education of Students in Higher Vocational Colleges based on Multiple Source Structure Types and Countermeasure Analysis - Wang, Youzhi (Journal of Theory and Practice of Contemporary Education, 2023)
Higher vocational students are in a critical period of ideological development, and ideological and political education is particularly important. Through the development of ideological and political education for higher vocational students, it can not only help them establish correct outlook on life and values, but also enable students to distinguish the truth from the current numerous information and realize the development of students' comprehensive ability. The ideological and political education based on a variety of student source structure types has significant application effects in the ideological and political education of higher vocational students, and is an important way to promote the development of students' ideological and political education ideas.